2008
DOI: 10.1038/ismej.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the gut microbiota of identical twins with Crohn's disease

Abstract: Increasing evidence suggests that a combination of host genetics and the composition of the gut microbiota are important for development of Crohn's disease (CD). Our aim was to study identical twins with CD to determine microbial factors independent of host genetics. Fecal samples were studied from 10 monozygotic twin pairs with CD (discordant n ¼ 6 and concordant n ¼ 4) and 8 healthy twin pairs. DNA was extracted, 16S rRNA genes were PCR amplified and T-RFLP fingerprints generated using general bacterial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
307
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(334 citation statements)
references
References 48 publications
23
307
3
1
Order By: Relevance
“…To ensure appropriate lysis of bacteria, the heating step was supplemented with three cycles of heating at 958C for 5 min followed by snap-freezing in liquid nitrogen. To obtain a profile of the faecal microbiota composition, extracted DNA was analysed with the T-RFLP methodology as previously described (Dicksved et al, 2008). Briefly, bacterial 16S rRNA gene fragments were PCR amplified from each DNA extract with general primers Bact-8F 5 0 -end labelled with 6-carboxyfluorescein and 926r.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure appropriate lysis of bacteria, the heating step was supplemented with three cycles of heating at 958C for 5 min followed by snap-freezing in liquid nitrogen. To obtain a profile of the faecal microbiota composition, extracted DNA was analysed with the T-RFLP methodology as previously described (Dicksved et al, 2008). Briefly, bacterial 16S rRNA gene fragments were PCR amplified from each DNA extract with general primers Bact-8F 5 0 -end labelled with 6-carboxyfluorescein and 926r.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Cloning and sequencing To identify bacteria that corresponded to TRFs of interest, small clone libraries from six pigs were created as previously described (Dicksved et al, 2008). Briefly, 16S rRNA gene fragments of the extracted DNA were amplified using primers Bact-8F and 926r.…”
Section: Sample Collectionmentioning
confidence: 99%
“…We have performed extensive studies on a Swedish twin cohort that include healthy individuals and individuals with different inflammatory bowel diseases (see more detail later). Our initial T-RFLP data revealed a high degree of similarity in the gut microbiota of identical twins, even when they lived apart for decades (Dicksved et al, 2008).…”
Section: The Host Interaction With the Gut Microbiomementioning
confidence: 99%
“…In this chapter we primarily discuss CD because of the large number of recent reports that have focused on the correlation of the gut microbiota to this particular disease. Different molecular fingerprinting techniques, including T-RFLP (Dicksved et al, 2008;Willing et al, 2009a), TGGE (Seksik et al, 2005), qPCR (Willing et al, 2009a), and 454 pyrosequencing (Willing et al, unpublished data), have revealed that the gut microbiota is different in individuals with CD compared to healthy individuals. This altered gut microbiota has been referred to as a state of "dysbiosis" (Seksik et al, 2005;Tamboli et al, 2004).…”
Section: Impact Of Diseasementioning
confidence: 99%
“…Culture‐independent technique has been used in microbiome studies of dog 19, 20. Culture‐independent technique approach allowed us to bypass the isolation and cultivation of individual species and improved our ability to identify obesity‐associated microbial changes in the gut 21, 22…”
mentioning
confidence: 99%